Pengaruh Brand Trust Dalam Memediasi Hubungan Antara Persepsi Kualitas Terhadap Niat Beli Laptop Asus - Ila Nurlita, Anggita; Anggarani W.P.T, Ari (CV. Lafadz Jaya, 2022)
This purpose of this research to determine the effect of perceived quality on purchase intention through brand trust on Asus laptops. Respondents in this study were active students of the Faculty of Economics and Business at Esa Unggul University Jakarta batch 2018-2021, with the criteria that they had seen and knew about the specifications and features of the Asus laptop brand. The sampling technique used in this study is a non-probability sampling method with a purposive sampling technique of 180 respondents using the formula Hair et.al (2013). The analytical method used is the Structural Equation Model (SEM) and uses Partial Least Square (PLS) to test the strength of direct and indirect relationships between various variables. The results of this study indicate that perceived quality has a positive effect on purchase intentions on Asus laptops. Brand trust has a positive effect on purchase intentions on Asus laptops. Perception of quality has a positive effect on brand trust on Asus laptops. Perception of quality on purchase intention has a positive effect mediated by brand trust on Asus laptops.